Analisis Kontrastivitas Mengenai Tense dan Aspek Bahasa Jepang dengan Bahasa Indonesia pada Majalah マイマイマガジン VOL .2 Edisi Oktober 2013 sampai Maret 2014 - Sulhiyah Sulhiyah (Faculty of Economics, Law, and Humanities, 2020)
Contrastive linguistics (対 象 言語 学 ish taishou-gengogaku ’) which is also calledcomparative linguistics is a linguistic study that is intended to describe two differentlanguages. Contrastive verbs are verbs that are derived from verbs to contras. ContranstiveAnalysis (Anakon) is an activity that attempts to compare the structure of language(B1) and structure of language (B2) to facilitate language differences. The purpose ofcontrastive linguistic study is to fnd out the form of contrastive analysis of tenses (Kala)and aspects of Japanese with Indonesian. In this study, the authors used a qualitativedescription which the translation was carried out using words or sentences that ft theresearch categories to obtain conclusions. The results showed that there are many markersof aspects and several tenses in Japanese, but in this study, only modality markers werediscussed which discussed the aspects of perfective, continuous aspects, and resultativeaspects. In certain contexts, researchers can still be confused about the marking aspectsof te as there are various aspects that can use these markers.